PENANGANAN DAN PENGUJIAN MUTU FISIK BENIH KALAPI (Kalappia celebica Kosterm) - Asrianti Arif; Alvin Alvin; Husna Husna; Faisal Danu Tuheteru (Universitas Haluoleo, 2018)
ABSTRACTKalapi (K.celebica Kosterm.) is an endemic and endangered plant species in Sulawesi and categorize as monotypic species in the Fabaceae family. Kalapi, since 1998, listed as endangered. However, researches about kalapi still limited, such research that related to the handling of the seeds, the dimensions of fruits and seeds, as well as testing of physical quality of seeds has not been done. So that, the purpose of this study was to determine handling of seeds, measuring the dimensions of fruits and seeds as well as testing of physical quality of seeds. Seed was collected from natural forest of Abuki, Village of Anggoro, District of Abuki, Konawe. Testing of physical quality of Kalapi was conducted at the Laboratory of Forestry, Faculty of Forestry and Environmental Sciences, Halu Oleo University, Kendari. Research was carried out for 4 months. Related to seed handling, technique to collect seed was by climbing and taking under trees. Physiologically, mature fruit has been colored brownish. Fruits that have been collected were stored in sacks and plastic. Fruits were extracted by using dry extraction. Based on, the dimensions of fruits and seeds observation, the length of the fruit averaged 7.081 cm (with ranged about 2.6-12.8 cm). While, the width of fruits has averaged 2.97 cm (with ranged about 1.7-4.6 cm). The mean length, width and thickness of each seed sized 11.33 mm (7.31-19.93 mm), 9.4 mm (5.99-11.90 mm) and 1.39 mm (0.7-2.02 mm), respectively. The number of seeds per fruit is 1-4 seeds. The average of purity of seeds that has been extracted is 99.51% with a range of 99.22-99.77%. Weight of 1000 of seeds grain is 99.1 g with a range of 91-103.6 g. Prediction of the number of seeds/kg is 10,113 grains of seeds / kg. Seeds moisture content is 13.12% with range of 11.3-13.12%. This research will support and provide important data about kalapi related to their seeds. Keywords: K. celebica Kosterm, character of seed physical, dimension of fruit and seed, Abuki.